Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. The reality of employing educational technologies in teaching students with disabilities from the point of view of teachers of special education Mr. Abdulrahman Khalaf Aldhafeeri 2. The role of the child’s theater in promoting national identity in early childhood according to the Kingdom’s vision 2030 from the point of view of teachers Mrs. Atheer Khudhayr Alharbi 3. The educational role of intellectual awareness units in Saudi universities in achieving intellectual immunity for its students Mrs. Retal Muhammad Asiri 4. Administrative empowerment among females’ leaders in secondary schools in Hafr Al-Batin and its social, cultural and environmental challenges Mrs. Mona Mutlaq Alanazi 5. The effectiveness of a proposed program based on communicative theory in teaching Arabic to develop digital intelligence skills for primary school students in Bisha Governorate Prof. Mahmoud Helal Abdelkader, Dr. Edrees Ali Matary 6. The reality of female high school principals exercising the dimensions of creative leadership in the governorate of one of the theaters "case study" Mrs. Ayshah Mahah Safhi 7. The relationship of academic resilience with positive thinking among female students at King Saud University Dr. Aeshah Mohammad Al-Khelaiwi, Co-Prof. Afaf Salem Al-Mohammadi